The Effect of Mindfulness Practices and Principal Leadership on Teacher Job Satisfaction at Buddhist Schools - Anna, Anna; Nyanasuryanadi, Partono; Burmansah, Burmansah (Scaffolding: Jurnal Pendidikan Islam dan Multikulturalisme, 2023)
This study was conducted to determine the results of mindfulness exercises with leader satisfaction with teacher work to show the importance of mindfulness in leadership. This study provides an overview of the impact of mindfulness practices and school leadership (principals) on school teachers' job satisfaction. This research was conducted at Tri Ratna Buddhist Private School, Jakarta, using a quantitative research approach with survey and questionnaire methods. The results of this study show the influence of Mindfulness practice on Teacher Job Satisfaction and the improvement of the principal's leadership ability affects teacher performance satisfaction at Tri Ratna School; this is because the principal provides clear examples and directions and helps solve various problems and provides examples in daily life in his leadership actions. This impacts the ability to manage stress and raise awareness, providing an excellent space for happiness and joy, supported by the principal's leadership ability, exemplary reflection, and clear direction.